Light-induced relaxing dipoles in n-type AlxGa1-xAs - Scalvi, Luis V. A. [UNESP]; Oliveira, Ligia De [UNESP]; Li, M. Siu (American Physical Society (APS), 1995)
Thermally stimulated depolarization-current measurements with monochromatic light excitation are applied to AlxGa1-xAs. We obtain conclusive evidence that electric-dipole relaxation occurs in this alloy. Light-induced relaxation of depolarization-current measurements show that relaxing dipoles have characteristics that are influenced by the wavelength of the monochromatic light. We associate these dipoles with a negatively charged DX-center ground state, since charge-relaxation currents are destroyed by photoionization of Al0.50Ga0.50As using either 647-nm Kr+ or 488-nm Ar+ laser lines. Correlation may exist among charged donor states, DX - d+. Ionization at the DX-center threshold photoionization energy, 0.8 eV, leads to a striking current-peak shift, which can be explained using a model that involves As vacancies. © 1995 The American Physical Society.